Hydrochemical characteristics and evaluation of surface water of Shatt Al-Hilla, Babil Governorate, Central Iraq - Manea, Mansoor Hussain; Al-Tawash, Balsam Salim; Al-Saady, Younus I. (Iraqi Journal of Science, 2019)
The current study aimed to assessing the water quality and discussing the hydrochemical characteristics and seasonal variation of surface water on the aspect of metals in Shatt-Al-Hilla, Babil Governorate, Central Iraq. Water samples were collected from eleven sampling sites of Shatt Al-Hila for wet season in March (18/3/2018), and a dry season in July (30/7/2018).Surface water samples were analyzed for physiochemical parameters such as water temperature pH, EC, TDS, major ions (Ca2+, Mg2+, Na+, K+, SO42-, Cl-, and HCO3-), nutrients (NO3-, and PO43-) for both seasons and DO for one season. Additionally, trace elements as Fe, B, Pb, Zn, Mn, Cr, Cu, Co, Ni, and Cd were also analyzed. Suitability of water for drinking and agricultural uses also evaluated.Shatt Al-Hilla water type was classified as Ca2+-HCO3- water type at wet season, and only (3) samples where Na+ is dominant than Ca2+ and classified as Na+-HCO3-. While at dry season, (6) samples classified as Na+-Cl- water type, and (5) samples where Ca+ is dominant than Na+ and classified as Ca2+-Cl-. Water classification based on Piper diagram shows that all samples are alkaline with increasing in the portions of alkalis and prevailing sulfate and chloride. Most water samples from Shatt Al-Hilla during the wet and dry seasons are unsuitable for drinking purposes according to results of anions and cations and trace elements, and within "excellent typeâ€ for livestock and poultry drinking and it lies within a permissible class based on EC limit for irrigation.